MICROSOFT 365 POWER POINT APPLICATION TRAINING AT COMDEV BINUS FOSTERY COMMUNITY - Dipa Nusantara, Pualam (Bina Nusantara University, 2023)
Presentation is one activity that has an important role in today's modern world. Conveying ideas and ideas in the right way can generate understanding and maintain audience interest. The importance of mastering the use of presentation applications is the basis of training for the community so that they bring more benefits to everyday life, both in work, education and social activities. The Microsoft 365 Power Point Application Training which was held on February 24, 2021 is expected to have an impact on community empowerment, especially by equipping them with mastery of the Power Point application that can be used at work.